Cancer Prognosis 2018
DOI: 10.5772/intechopen.78580
|View full text |Cite
|
Sign up to set email alerts
|

CBX4 Expression and AFB1-Related Liver Cancer Prognosis

Abstract: Background: Previous studies have shown that chromobox 4 (CBX4) expression may involve in the progression of liver cancer, however, it is unclear whether it affects the prognosis of hepatocellular carcinoma (HCC) related to aflatoxin B1 (AFB1). Methods: A retrospective study was conducted in the high AFB1 exposure areas and a total of 428 patients with HCC were included in the final survival analyses. AFB1 exposure levels and CBX4 expression in the tumor tissues were tested using enzyme-linked immunosorbent as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…This is because AFB1-DNA adducts are usually characterized by non-enzyme, time-dependence, and apparent persistence and can result in the activation of oncogenes (such as Ras) and the inactivation of tumor suppressor genes (such as TP53) [20,21]. Furthermore, amount of AFB1-DNA adducts in liver tissues are proved to positively correlate with tumor MVD [10]. Here, our data also showed that HCC patients with increasing amount of AFB1-DNA adducts would feature a shorten OS and RFS and an increased death risk and tumor recurrence risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because AFB1-DNA adducts are usually characterized by non-enzyme, time-dependence, and apparent persistence and can result in the activation of oncogenes (such as Ras) and the inactivation of tumor suppressor genes (such as TP53) [20,21]. Furthermore, amount of AFB1-DNA adducts in liver tissues are proved to positively correlate with tumor MVD [10]. Here, our data also showed that HCC patients with increasing amount of AFB1-DNA adducts would feature a shorten OS and RFS and an increased death risk and tumor recurrence risk.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because of rs77447679 SNP may regulate CBX4 expression and the dysregulation of CBX4 expression could promote tumor angiogenesis, increase tumor MVD, and affect tumor sensitivity on anti-cancer drugs [8,9]. An our recent study from high AFB1 exposure areas has displayed that increasing CBX4 protein expression in the tissues with HCC is significantly associated with poor survival of patients with AFB1-related HCC [10]. Taken together, these results suggest that CBX4 rs77447679 SNP may involve in the progression of HCC, especially cancer caused by AFB1 exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from clinicopathological studies has displayed that there is an increasing heterogenic expression profile of chromobox 4 (CBX4) in tumor tissular samples with HADA and this alteration statistically modifies the therapeutic efficiency of po-TACE treatment on HCC [ 19 ]. This may be result from the upregulation of CBX4 expression accelerating tumor angiogenesis and next inducing tumor proliferation and decreasing cancerous cells’ sensibility on anticancer drugs [ 14 , 19 , 36 ]. The present study furthermore proved that the levels of ADAs in tumor tissues were linked with tumor MVD.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular epidemiological studies conducted in high AFB1 exposure areas show that the genetic alterations in DNA repair genes (including XPC, XRCC4, XRCC1, and XPD) are not only associated with low DNA damage repair capacity and result in increasing amounts of ADAs, but also increase HCC risk and short survival of patients with HCC [15,[30][31][32][33]. For example, genetic alteration at the coding region of DNA repair gene XRCC4 increased the amount of ADAs in the HCC cells and change the sensibility of cancer cells on anticancer drug doxorubicin [34,35]. Third, ADAs maybe affect the process of tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%